Brexit is Done: What Next for UK Higher Education? - Corbett, Anne (International Higher Education, 2021)
This article reviews the implications of the Brexit deal for UK higher education and research. It argues that future scenarios will be based not only on the treaties signed with the European Union, but also on policy preferences as laid out in 2017 legislation on higher education and research, and two later policy decisions: to remain in the EU science and innovation program, and to enhance trading relationships, including higher education, with the Pacific region.